Surgical complications of peptic ulcer disease in Wad Madani teaching hospital June 2013 to june 2017 - yousif, Abuzer ali abdelgadir; Alsheikhl, Ahmad Alamin; Ahmad, Ahmad Kamal (Gezira Journal of Health Sciences; Vol 15 No 2 (2019), 2019)
Background: peptic ulcer disease is a common curable disease but still refractory and complicated disease  frequently seen. This study was done to identify the surgical complications of peptic ulcer disease, their clinical presentation , management and  outcome  . Objective: This study was carried out to identify types of surgical complications (bleeding, perforation and obstruction) , their clinical presentation ,site of the ulcer , intraoperative findings ,surgical procedure , postoperative complications and mortality   . Patients and methods : This was a cross-sectional  ( prospective and retrospective)  descriptive hospital based study of surgical complications of peptic ulcer disease  carried out at the departments of  surgery in Wad Medani Tteaching Hospital , Wad Medni, Sudan,  from June  2013 to June  2017. Data was collected from patients and hospital records using a designed questionnaire and analysed using SPSS version 21. Results: Ninety eight patients had surgical complications of peptic ulcer disease  were included in the study 71.4% (n=70) of them were males and 29.6% (n=28) were females with the male to female ratio 2.5 : 1   49%(n=48) were middle age group,73.5%(n=72) were from a rural areas the commonest clinical symptoms was epigasrtic pain 99% followed by vomiting 90.8% and heart burn 42.9% heamatemeisis was seen in 25.5% and the OGD showed that gastritis was the most common finding 46.4% followed by multiple ulcers and single ulcer and most of them were gastric , 42.9% were using NSAID and 72.4% had used antiulcer treatment the most common  surgical complication  was  perforation (84.7%) followed by gastric outlet obstruction 9.2% . and  bleeding  (6.1%) . (68 patient )   were treated with omental batch  ,15  with excision of the ulcer and repair, 9  with gastrojujenostomy and vagotomy,   4 with dudeonotomy and over sewing of bleeding vessel  and only  two patients were treated with partial gastrectomy. 23% developed complications of which sepsis was the commonest 55% and the mortality was 5.1% . Conclusion: Surgical complications of peptic ulcer  predominantly occurs in middle  age group  and males of rural area residents who were mostly  not diagnosed previously as peptic ulcer disease (PUD). The most common  complication seen was perforation  , GOO and bleeding. Outcome and mortality was greatly influenced by age , type of complication ,haematemesis,site of the ulcer , late presentation and the presence of sepsis . ملخص البحث                                                                                                   أجريت هذه الدراسة لإيضاح المضاعفات الجراحية للقرحة الهضمية  تناولت الأعراض السر يريه نوع المضاعفات  وطرق العلاج الجراحي التي اتبعت في مستشفى مدني التعليمي في الفترة من يونيو 2013 إلي يونيو 2017. تم تضمین 98 مريض  مضاعفات جراحیة لمرض القرحة الهضمية في الدراسة 71.4٪ (ن = 70) منھم ذکور و 29.6٪ (ن = 28) کانوا من الإناث وكان معدل الذکور إلی الإناث 2.5: 1  49٪ (ن = 48) كانت من الفئة العمرية المتوسطة، 73.5٪ (ن = 72) كانت من المناطق الريفية كانت الأعراض  السريرية الأكثر شيوعا ألم البطن 99٪ تليها القيء 90.8٪ وحرق القلب كان في 42.9٪  وجد القي الدموي  في 25.5٪ وأظهر منظار المعدة أن التهاب المعدة كان الأكثر شيوعا (46.7٪) تليها قرحة متعددة وقرحة واحدة، ومعظمهم في المعدة، و 42.9٪ كانوا يستخدمون مضادات الالتهاب غير الستيروئيدية، و 72.4٪ كانوا يستخدمون العلاج المضاد للقرحة   المضاعفات الجراحية الأكثر شيوعا هو ثقب القرحة (84.7٪) يليه انسداد مخرج المعدة 9.2 ٪. والنزيف (6.1٪). 68 مريضا تم علاجهم مع دفعة الأثينية، 15 مع استئصال القرحة  والإصلاح، 9 مع توصيل المعدة مع الصائم وقطع العصب الحائر ، 4 مع فتح ألاثني عشر والإفراط في الشريان النازف وتم علاج اثنين فقط من المرضى مع استئصال المعدة الجزئي  و 23٪ حدثت لهم مضاعفات ما بعد العملية التي كان الإنتان الأكثر شيوعا 55٪ وكان معدل الوفيات 5.1٪.